PERAN PASANGAN DALAM KEBERLANGSU PERAN PASANGAN DALAM KEBERLANGSUNGAN MENYUSUI : TINJAUAN SISTEMATIK STUDI KUALITATIF: PERAN PASANGAN DALAM KEBERLANGSUNGAN MENYUSUI : TINJAUAN SISTEMATIK STUDI KUALITATIF - Pratiwi, Bintang Agustina; Kartini, Apoina; Jati, Sutopo Patria; Sriatmi, Ayun (Universitas Airlangga, 2023)
Background: Breast milk is optimal for infant nutrition, and to ensure its sustained practice, maternal assistance from partners is essential, so that the breastfeeding process runs according to the expectations of the couple. Objectives: To identify the forms of support offered by partners for breastfeeding continuity. Methods: This research was conducted through a systematic review of qualitative research using three databases, namely PubMed, Scopus, and ScienceDirect, published from 2014 to 2023. The JBI Critical Appraisal Checklist for Qualitative Research was utilized to critically evaluate the included publications, resulting in the inclusion of five studies. Results: Within the breastfeeding context,